The Influence of Simping Clamshell Addition on Disc Brake Pad Mechanical Properties: Pengaruh Penambahan Kulit Kerang Simping terhadap Sifat Mekanik pada Kampas Rem Cakram - Agus Fikri; Firman Noor Hasan; Riyan Ariyansah (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2023)
The brake pads made from asbestos are environmentally hazardous due to the friction and abrasion occurring during braking, resulting in the release of airborne asbestos fibers. These fibers pose various health risks to humans and contribute to environmental pollution. This study aims to analyze the influence of adding clamshell waste material on the mechanical properties of motorcycle disc brake pads. The research utilized an experimental approach, conducting tensile and friction tests on six samples with different compositions: 100% brake pads, 40% brake pads, 60% simping clamshell, 60% brake pads, 40% simping clamshell, 20% brake pads, 80% simping clamshell, 50% brake pads, 50% simping clamshell, and 100% brake pads. The results indicate that the sample comprising 50% used brake pads and 50% simping clamshell exhibited the smallest difference in thickness, measuring 0.05 mm or 0.59%, indicating the strongest adhesive strength and wear resistance compared to other variations. Thus, a higher simping clamshell composition sacrifices some tensile strength but offers improved elasticity, benefiting specific braking conditions.